Detection of unsoundness and vice in horses - Ross, John F. (My University, 1902)
Introduction: What is soundness? Just what is meant by a sound horse is a much disputed question. Many litigations have arisen over the interpretation of the word. Veterinarians as a rule have very little knowledge of law and lawyers know less about veterinary subjects and hence it is difficult for them to agree upon a definition of soundness. Strictly speaking, sound, means without imperfection or blemish but such a condition is seldom if ever met with. Veterinarians define soundness from a medical point of view; lawyers look at it differently and the predominating idea among them is that a horse is sound if he is able to perform in a satisfactory way the work for which he is fitted by nature. The latter definition, though commonly accepted, is dangerous and many deceptions are fostered by it. Unsoundness is any deviation from the normal state and is therefore the perfection of animal health and form. Taplin in one of his books writes “A sound horse should possess a perfect state of both frame and bodily health, without exception or ambiguity, the total absence of blemishes as well as defects, and freedom from every imperfection and all impediments to slight and action”. The adoption of such a standard as this would put an end to much of the useless expenditure in lawyer’s fees. Lawyers realize this and insist in defining soundness in a compromising way. In this article the definition will be given its strictest interpretation, very aptly expressed in the above words of Taplin. This stand is taken on the ground that if the buyer be able to detect unsoundness he can also judge the degree to which the animals usefulness is impared.
Citation: Ross, John F. Detection of unsoundness and vice in horses. Senior thesis, Kansas State Agricultural College, 1902.
Morse Department of Special Collections
Keywords: Equine; Soundness; Horses; Theses